Training volume recommendations and psychosocial outcomes in adolescent athletes - Little, C. C.; Howell, D. R.; Armento, A. M.; Sweeney, E. A.; Walker, G. A. (The Physician and Sportsmedicine, 2023)
Objectives Researchers have recommended that youth athletes limit their practice volume to the number of hours/week that they are old in years. We examined sport perceptions, burnout, anxiety, and depressive symptoms among youth athletes who did and did not report playing more hours/week of organized sports than their age.